"That's Not Very Deleuzian": Thoughts on interrupting the exclusionary nature of "High Theory". Issue 1 (2nd January 2018) - Strom, Kathryn J.
Abstract: In the following essay, I discuss my own uneasy and nonlinear journey from the classroom to Deleuze, describing the concepts and lines of thought that have been productive in thinking differently about teaching and teacher education. I also detail my encounters with the surprising orthodoxies of using Deleuzian/Deleuzoguattarian thought. From these, I suggest that 'being Deleuzian' is itself a molar line that serves as an exclusionary mechanism, working to preserve high theory for the use of only a select few. Instead, I argue for the potential of making such nonlinear thinking accessible to mainstream audiences to interrupt the linear, status quo thinking undergirding a global educational neoliberal movement.